Pengukuran Potensi Kerugian Pembiayaan Berbasis Profit and Loss Sharing (PLS) dengan Pendekatan Value At Risk (VAR) - Anggraeni, Rr Tini (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
Sharia Banks have uncertain returns. This is because Islamic banks cannot determine with certainty at the beginning how much return must be determined at the beginning. The yield obtained is adjusted to the acquisition of revenue from Shahibul Mall. Uncertain yields certainly have the potential for uncertain gains and losses. Uncertain yields are most felt in mudharabah and musyarakah financing based on Profit and Loss Sharing (PLS). The high return is in line with the high risk. Based on preliminary observations, mudharabah and musyarakah financing have higher returns compared to other types of financing. For this reason, it is necessary to measure the potential losses faced by mudharabah and musyarakah financing so that depositors and shahibul mal customers can predict the rate of return generated on mudharabah and musyarakah financing. Using the Value at Risk (VAR) approach, it is hoped that the results of this study can be used as a reference for decision makers to determine the equivalent rate of profit sharing that can be used as a reference in placing funds, especially in mudharabah and musyarakah financing.